Towards a Meta-Social-Ecological System Perspective: A Response to Gounand et al - Renaud, Pierre-Cyril; de O. Roque, Fabio; Souza, Franco L.; Pays, Olivier; Laurent, François; Fritz, Hervé; Fischer, Erich; Fabricius, Christo (Trends in ecology & evolution (Amsterdam), 2018)
The meta-ecosystem approach has significantly advanced ecosystem science and landscape ecology by explicitly addressing the flow of elements (live organisms, biotic and abiotic materials) among ecosystems at different temporal and spatial scales [1,2]. Gounand et al. [3] recently argued that the conciliation of theoretical and empirical studies on meta-ecosystems needs better quantification of spatial flows in terms of movements (dispersal, foraging, life-cycle, and migration), feedbacks, and resources.